Treatment of Bone Marrow Edema of the Foot and Ankle With the Prostacyclin Analog Iloprost. (October 2018) - Hörterer, Hubert; Baumbach, Sebastian Felix; Gregersen, Johanne; Kriegelstein, Stefanie; Gottschalk, Oliver; Szeimies, Ulrike; Walther, Markus
Background: Bone marrow edema (BME) of the foot and ankle is challenging to treat. One approach is intravenous Iloprost treatment, which is a vasoactive prostacyclin analog. The aim of this study was to evaluate the early and intermediate outcome of intravenous Iloprost therapy on BME of the foot and ankle and to analyze the influence of its etiology and Association Research Circulation Osseous (ARCO) stage on the outcome. Methods: This was a retrospective study with prospective follow-up. All patients treated by intravenous Iloprost for BME of the foot and ankle (ARCO I-III) at a single orthopedic reference center were included. Demographics, medical history, and MRIs were assessed prior to treatment (t0). MRIs were used to assess the BMEs' etiology (idiopathic/ischemic/metabolic, mechanical/degenerative, traumatic) and severity (ARCO). Complications as well as changes in pain, treatment, and MRI were evaluated after 3 months (t1). The following patient-rated outcome measures (PROMs) were assessed prospectively (t2): 12-Item Short Form Health Survey (SF-12), Visual Analog Scale Foot and Ankle (VAS FA), and the Foot Function Index (FFI) (also at t0). The descriptive outcomes and the influence of the etiology and ARCO on the outcome parameters were evaluated. Out of 70 eligible patients, 42 patients (60%; 47 ± 15 years; 30% female) with a mean follow-up of 28 ± 19 months were included. Results: Twelve patients reported minor complications during Iloprost therapy. At t1, pain decreased significantly in 56%, and the amount of BME decreased in 83% of patients. Both parameters correlated moderately (r = −0.463, P = .015). The PROMs at t2 revealed moderate results. The overall FFI improved from 59 ± 21 to 30 ± 22 ( P < .001), the overall VAS FA was 68 ± 20, the SF-12 Physical Component Summary 42 ± 12 and Mental Component Summary 50 ± 9. Subgroup analysis revealed no significant influence of the etiology or ARCO stage on any outcome measure. Conclusion: Iloprost therapy for BME of the foot and ankle resulted in a 60% pain and 80% edema decrease after 3 months. After 2 years, patient-rated outcome measures showed residual impairment. Neither the etiology nor ARCO stage significantly influenced the outcome. Level of Evidence: Level III, comparative study.